PENGARUH SUASANA TOKO DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN - Wawan Kuswandana; Tjiptodjojo, Kartika Imasari (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
Good store atmosphere and service quality can support the success of a business in reaching consumers who have the desire and action to make repeated purchases. This research focuses on how store atmosphere and service quality can affect customer loyalty. Data were collected through questionnaires distributed to 145 respondents, who had shopped at least five times at the Griya Setrasari supermarket, in Bandung City. Data analysis used linear regression analysis and the results showed that store atmosphere and service quality contributed 38.5% to customer loyalty. Recommendations are aimed at improving store atmosphere elements and employee training to create a satisfying shopping experience.